The asymptotic behaviour of trajectories dissipative quadratic stochastic operators 2D simplex - Shahidi, Farruh; Md Tap, Abu Osman (World Science Publishing Company, 2012)
We study the limit behavior of dissipative quadratic stochastic operators on 2D simplex. We show that dissipative quadratic stochastic operator, which is not linear, is either regular or has infinitely many fixed points. If the dissipative quadratic stochastic operator is regular, it is shown that its unique fixed point is either a vertex of a simplex or the center of the face of the simplex